Denitration catalyst coal gangue matrix with high specific surface area and preparation method of denitration catalyst coal gangue matrix

By using the mixing and high temperature activation of coal gangsters and flour ash and red mud to prepare a high -ratio surface area and low -cost denitration catalyst coal gangue base, solve the problem of high matrix cost and smaller surface area in the existing technology, realize High -efficiency, economical denitration catalyst system preparation.

CN119346147APending Publication Date: 2025-01-24XIAN RES INST OF CHINA COAL TECH & ENG GRP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411349121.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing denitrification catalyst matrix is ​​expensive and the specific surface area of ​​some matrix is ​​small, which limits the promotion and application of denitrification catalysts.

Method used

Using coal gangue as the matrix, through mixing with fly ash and red mud and high-temperature activation treatment, combined with ball milling, drying and impregnation steps, a high specific surface area, low-cost denitrification catalyst gangue matrix is ​​prepared.

Benefits of technology

The preparation of denitration catalyst substrate with high specific surface area and low cost is achieved, which reduces the production cost, is suitable for industrial scale application, and meets the requirements of circular economy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005061829560000091
    Figure BDA0005061829560000091
  • Figure BDA0005061829560000101
    Figure BDA0005061829560000101
  • Figure BDA0005061829560000102
    Figure BDA0005061829560000102
Patent Text Reader

Abstract

The invention provides a high-specific-surface-area denitration catalyst coal gangue matrix and a preparation method thereof.The preparation method comprises the steps that a coal gangue raw material is sequentially subjected to crushing, screening and high-temperature activating treatment, and coal gangue powder is obtained; the preparation method comprises the following steps: mixing coal gangue powder, fly ash and red mud according to a formula ratio to obtain a mixed material, and sequentially carrying out ball milling, drying and screening treatment on the mixed material to obtain a coal gangue matrix precursor; the mass ratio of the activated fly ash powder to the kaolin to the CeO2 is (2.9 to 3.7) to (0.4 to 0.5) to (0.8 to 1.2); the coal gangue matrix precursor is soaked in an aluminum salt solution to stand for 16-18 h, then drying is conducted for 12-15 h at the temperature of 80-120 DEG C, roasting is conducted for 4-6 h at the temperature of 450-500 DEG C in sequence, and coal gangue matrix powder is prepared; sodium carboxymethyl cellulose, polyoxyethylene, glass fiber, water-soluble kapok, diatomite, silicon carbide, hydroxymethyl cellulose, phenolic resin and water are added into the coal gangue matrix powder according to the formula ratio, extrusion molding is performed through an extruder, and the coal gangue composite material is prepared. According to the invention, resource recycling of the fly ash is realized, and the production cost of the denitration catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and relates to a denitration catalyst matrix, and in particular to a high specific surface area denitration catalyst gangue matrix and a preparation method thereof. Background Art

[0002] Gangue is one of the by-products of the coal industry, with huge annual output and reserves. Gangue is hard in texture, and its components include SiO2, Al2O3, Fe2O3 and heavy metal ions, etc. It has the characteristics of high ash content and low calorific value. At present, gangue is mainly used in filling subsidence areas, building materials, power generation and chemical industries. However, the output of gangue is still greater than the consumption, making gangue one of the industrial solid wastes with the largest emissions. The accumulation of gangue not only occupies a large amount of land resources, but also pollutes the ecological environment such as the atmosphere, water bodies and soil. The comprehensive utilization of gangue has always been a hot issue for researchers to explore.

[0003] The substrates of existing coated denitrification catalysts are mainly molecular sieves, cordierite, vermiculite, etc. These substrates have good performance, but the defects are: some substrates have small specific surface areas; some substrates, such as cordierite and vermiculite substrates, are expensive, which limits the promotion and application of denitrification catalysts. It is urgent to develop denitrification catalyst substrates with large specific surface areas, large pores and low prices. How to make full use of the multi-active component coexistence layered structure of coal gangue, improve the dispersion of catalytic active sites, and achieve coal gangue emission reduction and efficiency improvement is of great significance. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a coal gangue matrix of a denitrification catalyst with a high specific surface area and a preparation method thereof. The preparation method uses solid waste fly ash as the main raw material, utilizes the complementary characteristics of the advantages and disadvantages of each component after compounding, and obtains a denitrification catalyst matrix with a high specific surface area and low cost.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0006] A method for preparing a coal gangue matrix of a high specific surface area denitration catalyst comprises the following steps:

[0007] Step 1, crushing, screening, and high-temperature activation treatment are performed on the coal gangue raw materials in sequence to obtain coal gangue powder;

[0008] Step 2, mixing the formulated amount of coal gangue powder, fly ash and red mud to obtain a mixed material, and the mixed material is successively subjected to ball milling, drying and sieving to obtain a coal gangue matrix precursor;

[0009] In the mixed material, the mass ratio of coal gangue powder, fly ash and red mud is (2.9-3.7):

[0010] (0.4~0.5):(0.8~1.2);

[0011] Step 3, immersing the gangue matrix precursor in an aluminum salt solution and standing for 16 to 18 hours, then drying at 80 to 120° C. for 12 to 15 hours and calcining at 450 to 500° C. for 4 to 6 hours to obtain a gangue matrix powder;

[0012] Step 4, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the gangue matrix powder obtained in step 3, and extruding the mixture through an extruder to obtain a high specific surface area denitration catalyst gangue matrix;

[0013] The high specific surface area denitration catalyst gangue matrix comprises the following components in mass percentage: 68.5% to 72.0% of gangue matrix powder, 0.4% to 0.8% of sodium carboxymethyl cellulose, 0.2% to 0.5% of polyethylene oxide, 1.8% to 2.0% of glass fiber, 0.6% to 0.8% of water-soluble kapok, 0.8% to 1.0% of diatomaceous earth, 1.0% to 1.3% of silicon carbide, 0.8% to 1.5% of hydroxymethyl cellulose, 2.2% to 4.2% of phenolic resin and 19.5% to 20.0% of water, and the mass percentage of each component totals 100%.

[0014] The present invention also has the following technical features:

[0015] Specifically, the temperature of the high temperature activation treatment in step 1 is 600-700° C., and the particle size of the fly ash is ≤0.15 mm.

[0016] Furthermore, in step 2, the ball milling treatment includes: placing the mixed material in a planetary ball mill, ball milling at a speed of 300 to 600 r / min for 6 to 12 hours, adding deionized water to the planetary ball mill during the ball milling process, and the mass ratio of the mixed material to the deionized water is (2.0 to 4.0): 1.0; the temperature of the drying treatment is 70 to 110° C., and the drying time is 0.5 to 1 hour;

[0017] Furthermore, the aluminum salt described in step 3 is Al(NO3)3·nH2O, where n=0, 1, 2, ..., 9.

[0018] Furthermore, in step 3, the mass ratio of the gangue matrix precursor to the aluminum salt is (2.0-3.0):1.0, and during impregnation, the mass ratio of the gangue matrix precursor to the ionized water in the aluminum salt solution is: 1:(1.0-1.5).

[0019] Furthermore, the step 4 specifically includes the following sub-steps:

[0020] Step 4.1, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the coal gangue matrix powder, and stirring for 4 to 6 hours to obtain a mixture A;

[0021] Step 4.2, wrapping the mixture A with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture B;

[0022] Step 4.3, kneading the mixture B in a vacuum environment of 0.09-0.10 MPa to obtain a mixture C;

[0023] Step 4.4, wrapping the mixture C with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture D;

[0024] Step 4.5, kneading the mixture B in a vacuum environment with a vacuum degree of 0.09 MPa to 0.10 MPa to obtain a mixture E;

[0025] Step 4.6, placing the mixture E into a vacuum extruder, and extruding it at an extrusion pressure of 3.6 to 5.0 MPa and an extrusion speed of 500 mm / min to 1000 mm / min to obtain a green body;

[0026] Step 4.7, drying the green body at 50° C. to 80° C. for 2 to 5 hours until the moisture content of the green body is less than 2%, thereby obtaining a dried green body;

[0027] Step 4.8, keeping the dried body at 500°C to 550°C for 8h to 12h to obtain a coal gangue matrix.

[0028] The present invention also protects a high specific surface area denitration catalyst gangue matrix, and the gangue matrix is ​​prepared by the above-mentioned preparation method.

[0029] Compared with the prior art, the present invention has the following technical effects:

[0030] (1) The main solid raw material used in the preparation method provided by the present invention is solid waste coal gangue, which fully utilizes the characteristics of coal gangue such as large specific surface area, high porosity, high hardness, and large stock, and obtains a high specific surface area and low-cost denitration catalyst coal gangue matrix, thereby realizing the resource recycling of solid waste coal gangue, reducing the production cost of the denitration catalyst, and facilitating the further promotion of the denitration catalyst, and better meeting the strategic requirements of the development of the circular economy.

[0031] (2) The raw materials used in the method of the present invention are cheap, the process is simple, the conditions are mild, and it is suitable for industrial-scale development and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a sample of the coal gangue matrix obtained in Example 1;

[0033] Figure 2 This is a sample diagram of coal gangue matrix mass-produced by the method of the present invention;

[0034] Figure 3 The following are SEM images of the products obtained in Examples 1 to 3, Comparative Example 1 and Comparative Example 2.

[0035] The specific contents of the present invention are further described in detail below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by any ordinary technician in the field belong to the scope of protection of the present invention.

[0037] It should be noted that all raw materials in the present invention, unless otherwise specified, are raw materials known in the art.

[0038] The technical concept of this application is: using the characteristics of coal gangue as solid waste, such as large specific surface area, high porosity, high hardness, and large stock, to prepare a coal gangue matrix of a denitration catalyst; wherein, the large specific surface area and high porosity of coal gangue can ensure that the denitration catalyst matrix has a high specific surface area and active sites; the high hardness of coal gangue can ensure that the denitration catalyst matrix is ​​not easily eroded and worn by flue gas; the large stock of coal gangue can ensure that the production and manufacturing cost of the denitration catalyst matrix is ​​low. It is precisely because of the many characteristics of coal gangue that products with high specific surface area can be successfully obtained.

[0039] The coal gangue used in the present invention is mainly composed of Si and Al, including the following raw material components, in terms of mass percentage, Al2O3 36.54% to 40.25% and SiO2 57.35% to 59.15%, and the rest are impurities and loss on ignition, and the mass percentage of each component totals 100%.

[0040] According to the above technical scheme, the present invention discloses a method for preparing a coal gangue matrix of a denitration catalyst with a high specific surface area, and a method for preparing a coal gangue matrix of a denitration catalyst with a high specific surface area, comprising the following steps:

[0041] Step 1, subjecting the fly ash raw material to high temperature activation treatment to obtain activated fly ash powder;

[0042] Preferably, the temperature of the high-temperature activation treatment is 600-700° C., and the particle size of the fly ash is ≤0.15 mm.

[0043] Step 2, mixing the formulated amount of coal gangue powder, fly ash and red mud to obtain a mixed material, and the mixed material is successively subjected to ball milling, drying and sieving to obtain a coal gangue matrix precursor;

[0044] In the mixed material, the mass ratio of coal gangue powder, fly ash and red mud is (2.9-3.7):

[0045] (0.4~0.5):(0.8~1.2);

[0046] Preferably, the ball milling treatment comprises: placing the mixed material in a planetary ball mill, ball milling at a speed of 300 to 600 r / min for 6 to 12 hours, adding deionized water to the planetary ball mill during the ball milling process, and the mass ratio of the mixed material to the deionized water is (2.0 to 4.0): 1.0;

[0047] The drying temperature is 70-110°C and the drying time is 0.5-1h;

[0048] Step 3, immersing the gangue matrix precursor in an aluminum salt solution and standing for 16 to 18 hours, then drying at 80 to 120° C. for 12 to 15 hours and calcining at 450 to 500° C. for 4 to 6 hours to obtain a gangue matrix powder;

[0049] Preferably, the aluminum salt is Al(NO3)3·nH2O, where n=0, 1, 2, ..., 9.

[0050] Preferably, in step 3, the mass ratio of the gangue matrix precursor to the aluminum salt is (2.0-3.0):1.0, and during impregnation, the mass ratio of the gangue matrix precursor to the ionized water in the aluminum salt solution is: 1:(1.0-1.5).

[0051] Step 4, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the gangue matrix powder obtained in step 3, and extruding the mixture through an extruder to obtain a high specific surface area denitration catalyst gangue matrix;

[0052] It includes the following sub-steps:

[0053] Step 4.1, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the coal gangue matrix powder, and stirring for 4 to 6 hours to obtain a mixture A;

[0054] Step 4.2, wrapping the mixture A with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture B;

[0055] Step 4.3, kneading the mixture B in a vacuum environment of 0.09-0.10 MPa to obtain a mixture C;

[0056] Step 4.4, wrapping the mixture C with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture D;

[0057] Step 4.5, kneading the mixture B in a vacuum environment with a vacuum degree of 0.09 MPa to 0.10 MPa to obtain a mixture E;

[0058] Step 4.6, placing the mixture E into a vacuum extruder, and extruding it at an extrusion pressure of 3.6 to 5.0 MPa and an extrusion speed of 500 mm / min to 1000 mm / min to obtain a green body;

[0059] Step 4.7, drying the green body at 50° C. to 80° C. for 2 to 5 hours until the moisture content of the green body is less than 2%, thereby obtaining a dried green body;

[0060] Step 4.8, keeping the dried body at 500°C to 550°C for 8h to 12h to obtain a coal gangue matrix.

[0061] Among them, the high specific surface area denitrification catalyst coal gangue matrix includes the following components in mass percentage: 68.5% to 72.0% coal gangue matrix powder, 0.4% to 0.8% sodium carboxymethyl cellulose, 0.2% to 0.5% polyethylene oxide, 1.8% to 2.0% glass fiber, 0.6% to 0.8% water-soluble kapok, 0.8% to 1.0% diatomaceous earth, 1.0% to 1.3% silicon carbide, 0.8% to 1.5% hydroxymethyl cellulose, 2.2% to 4.2% phenolic resin and 19.5% to 20.0% water, and the mass percentage of each component totals 100%.

[0062] Specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical solution of this application fall within the protection scope of the present invention.

[0063] Example 1

[0064] In accordance with the above technical scheme, this embodiment provides a method for preparing a method for preparing a coal gangue matrix of a high specific surface area denitration catalyst, which specifically comprises the following steps:

[0065] Step 1: crush the gangue raw material with a crusher, screen it with a 100-mesh screen, and activate it at a high temperature of 700° C. to obtain gangue powder with a particle size of ≤0.15 mm;

[0066] Step 2: Mix gangue powder, fly ash and red mud in a mass ratio of 2.9:0.4:0.8 to obtain a mixed material, and then use a ball mill to ball mill the mixed material at a ball mill speed of 500r / min for 10h; dry the mixed material at 90°C for 30min; and sieve the dried mixed material with a 100-mesh sieve to obtain a precursor of a gangue matrix;

[0067] Step 3: According to the mass ratio of the precursor to the aluminum salt being 2.0:1.0 and the mass ratio of the precursor to the ionized water being 1.0:1.5, the precursor is immersed in an aluminum salt solution, and then allowed to stand for 24 hours, dried at 110° C. for 12 hours, and calcined at 500° C. for 6 hours to obtain a coal gangue matrix powder;

[0068] Step 4, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the coal gangue matrix powder, extruding and molding through an extruder to obtain a high specific surface area denitration catalyst coal gangue matrix;

[0069] Among them, by mass percentage, the coal gangue matrix powder is 70.5%, sodium carboxymethyl cellulose 0.6%, polyethylene oxide 0.3%, glass fiber 1.8%, water-soluble kapok 0.8%, diatomaceous earth 0.9%, silicon carbide 1.1%, hydroxymethyl cellulose 1.0%, phenolic resin 3% and water 20.0%.

[0070] Figure 1 The high specific surface area denitration catalyst gangue matrix sample was prepared in the laboratory according to the method of this embodiment. Figure 1 It has been proved that the method of the present invention is feasible. Figure 2 This is a sample of a coal gangue matrix of a denitration catalyst with a high specific surface area mass-produced according to the method of this embodiment, which indicates that the coal gangue matrix of a denitration catalyst with a high specific surface area of ​​the present invention can be successfully applied in industry.

[0071] The compressive strength test of the high specific surface area denitration catalyst coal gangue matrix prepared in this embodiment was carried out using a YAW-100 pressure testing machine, with a loading speed of 1.125 kN / s; the wear performance was tested in a homemade device according to the requirements of GB / T 31587-2015 "Honeycomb Flue Gas Denitration Catalyst". The matrix was cut into 5×5 holes, dried at 105°C for 2h, and placed in the test sample and the comparison sample respectively after cooling. The wind speed was 14.5m / s and the quartz sand concentration was 52g / m 3 The detection time is 2h.

[0072] The BET characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table 1; the SEM characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table Figure 3As shown; the cost calculation results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 2; the performance test results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 3.

[0073] Example 2

[0074] This embodiment discloses a method for preparing a low-cost, high-specific surface area denitrification catalyst and a high-specific surface area denitrification catalyst coal gangue matrix. The steps of the method are the same as those of Example 1, except that in step 2, the mass ratio of coal gangue powder, fly ash and red mud is 3.3:0.45:1.0.

[0075] The BET characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table 1; the SEM characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table Figure 3 As shown; the cost calculation results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 2; the performance test results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 3.

[0076] Example 3

[0077] This embodiment discloses a method for preparing a low-cost, high-specific surface area denitrification catalyst and a high-specific surface area denitrification catalyst coal gangue matrix. The steps of the method are the same as those of Example 1, except that in step 2, the mass ratio of coal gangue powder, fly ash and red mud is 3.7:0.5:1.2.

[0078] The BET characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table 1; the SEM characterization results of the high specific surface area denitration catalyst coal gangue matrix of this embodiment are shown in Table Figure 3 As shown; the cost calculation results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 2; the performance test results of the high specific surface area denitration catalyst gangue matrix of this embodiment are shown in Table 3.

[0079] Comparative Example 1

[0080] The commercial V / TiO2 catalyst matrix is ​​practically formed in this comparative example.

[0081] The commercial V / TiO2 catalyst matrix of this comparative example was characterized by BET, and the results are shown in Table 1;

[0082] The commercial V / TiO2 catalyst matrix of this comparative example was characterized by SEM. Figure 3 As shown:

[0083] The cost of the commercial V / TiO2 catalyst matrix of this comparative example was calculated and the results are shown in Table 2.

[0084] The performance of the commercial V / TiO2 catalyst matrix of this comparative example was tested, and the results are shown in Table 3.

[0085] Comparative Example 2

[0086] This comparative example provides a denitration catalyst TiO2 matrix, which is prepared by the molding process disclosed in step 4 of the method of the present invention. The difference is that in this comparative example, the high specific surface area denitration catalyst coal gangue matrix powder is replaced by TiO2 matrix powder.

[0087] The denitration catalyst TiO2 matrix provided in this comparative example was characterized by BET, and the specific results are shown in Table 1;

[0088] The denitration catalyst TiO2 matrix provided in this comparative example was characterized by SEM. The specific results are as follows Figure 3 As shown:

[0089] The cost of the TiO2 substrate of the denitration catalyst provided in this comparative example was calculated, and the results are shown in Table 2.

[0090] The performance of the denitration catalyst TiO2 matrix provided in this comparative example was tested, and the results are shown in Table 3.

[0091]

[0092]

[0093] Table 1. Parameters of the substrates obtained in Examples 1 to 3, Comparative Examples 1 and 2

[0094] The size of the specific surface area determines the number of active sites on the catalyst surface, and the number of active sites determines the catalyst activity. It can be seen from Table 1 that the high specific surface area denitration catalyst gangue matrix prepared in Examples 1 to 3 has a large specific surface area, which is larger than the commonly used commercial catalyst and slightly smaller than TiO2. The test results of the specific surface area are the same as the SEM characterization results. It can be seen from the scanning electron microscope that the surface particle size of the high specific surface area denitration catalyst gangue matrix prepared in Examples 1 to 3 and the matrix prepared in Comparative Examples 1 and 2 are relatively uniform, and the particle size comparison is Comparative Example 1> Example 1≈ Example 2≈ Example 3> Comparative Example 2. The particle size determines the specific surface area of ​​the matrix, so SEM also proves that the high specific surface area denitration catalyst gangue matrix prepared in this scheme has a large specific surface area, which is much larger than the commercial catalyst and slightly smaller than TiO2.

[0095]

[0096] Table 2. Matrix preparation costs of Examples 1 to 3, Comparative Examples 1 and 2.

[0097] It can be seen from Table 2 that the preparation costs of Examples 1 to 3 are much lower than those of Comparative Examples 1 and 2, which demonstrates the cost advantage of the high specific surface area denitration catalyst coal gangue matrix and reduces the production cost of the denitration catalyst.

[0098]

[0099]

[0100] Table 3. Test results of mechanical parameters of substrates of Examples 1 to 3, Comparative Examples 1 and 2

[0101] (The test substrate is a 30-hole honeycomb substrate, the component parameters are 150mm×150mm×740mm, and the porosity is 72.4%)

[0102] It can be seen from Table 3 that the axial compressive strength and radial compressive strength of the high specific surface area deNOx catalyst coal gangue matrix prepared in Examples 1 to 3 are significantly greater than the matrix provided by Comparative Examples 1 and 2, while the wear strength is significantly lower than the matrix provided by Comparative Examples 1 and 2, which can better meet application requirements.

[0103] In summary, the main solid raw material used in the high specific surface area denitrification catalyst gangue matrix provided by the present invention is solid waste gangue. By utilizing the characteristics of gangue such as large specific surface area, high porosity, high hardness and large stock, a high specific surface area denitrification catalyst gangue matrix is ​​finally prepared, which increases the utilization rate of solid waste and reduces the production cost of the denitrification catalyst.

[0104] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0105] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a high specific surface area denitration catalyst coal gangue matrix, characterized in that: The following steps are involved: Step 1, crushing, screening, and high-temperature activation treatment are performed on the gangue raw materials in sequence to obtain gangue powder; Step 2: Mix the formulated amount of gangue powder, fly ash and red mud to obtain a mixed material, and the mixed material is successively subjected to ball milling, drying and sieving to obtain a gangue matrix precursor; In the mixed material, the mass ratio of coal gangue powder, fly ash and red mud is (2.9-3.7): (0.4~0.5):(0.8~1.2); Step 3, immersing the gangue matrix precursor in an aluminum salt solution and standing for 16 to 18 hours, then drying at 80 to 120° C. for 12 to 15 hours and calcining at 450 to 500° C. for 4 to 6 hours to obtain a gangue matrix powder; Step 4, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the gangue matrix powder obtained in step 3, and extruding the mixture through an extruder to obtain a high specific surface area denitration catalyst gangue matrix; The high specific surface area denitration catalyst gangue matrix comprises the following components in mass percentage: 68.5% to 72.0% of gangue matrix powder, 0.4% to 0.8% of sodium carboxymethyl cellulose, 0.2% to 0.5% of polyethylene oxide, 1.8% to 2.0% of glass fiber, 0.6% to 0.8% of water-soluble kapok, 0.8% to 1.0% of diatomaceous earth, 1.0% to 1.3% of silicon carbide, 0.8% to 1.5% of hydroxymethyl cellulose, 2.2% to 4.2% of phenolic resin and 19.5% to 20.0% of water, and the mass percentage of each component totals 100%.

2. The method for preparing a high specific surface area denitration catalyst coal gangue matrix according to claim 1, characterized in that: The temperature of the high temperature activation treatment in step 1 is 600-700° C., and the particle size of the fly ash is ≤0.15 mm.

3. The method for preparing a coal gangue matrix of a high specific surface area denitration catalyst according to claim 1, characterized in that: In step 2, the ball milling treatment includes: placing the mixed material in a planetary ball mill, ball milling at a rotation speed of 300 to 600 r / min for 6 to 12 hours, adding deionized water to the planetary ball mill during the ball milling process, and the mass ratio of the mixed material to the deionized water is (2.0 to 4.0): 1.0; the temperature of the drying treatment is 70 to 110° C., and the drying time is 0.5 to 1 hour.

4. The method for preparing a coal gangue matrix of a high specific surface area denitration catalyst according to claim 1, characterized in that: In step 2, the aluminum salt described in step 3 is Al(NO3)3·nH2O, where n=0, 1, 2, ..., 9.

5. The method for preparing a coal gangue matrix of a high specific surface area denitration catalyst according to claim 1, characterized in that: In step 3, the mass ratio of the gangue matrix precursor to the aluminum salt is (2.0-3.0):1.0, and during impregnation, the mass ratio of the gangue matrix precursor to the ionized water in the aluminum salt solution is: 1:(1.0-1.5).

6. The method for preparing a coal gangue matrix of a high specific surface area denitration catalyst according to claim 1, characterized in that: The step 4 specifically includes the following sub-steps: Step 4.1, adding a formula amount of sodium carboxymethyl cellulose, polyethylene oxide, glass fiber, water-soluble kapok, diatomaceous earth, silicon carbide, hydroxymethyl cellulose, phenolic resin and water to the coal gangue matrix powder, and stirring for 4 to 6 hours to obtain a mixture A; Step 4.2, wrapping the mixture A with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture B; Step 4.3, kneading the mixture B in a vacuum environment of 0.09-0.10 MPa to obtain a mixture C; Step 4.4, wrapping the mixture C with a plastic wrap and aging it at room temperature for 12 to 24 hours to obtain a mixture D; Step 4.5, kneading the mixture B in a vacuum environment with a vacuum degree of 0.09 MPa to 0.10 MPa to obtain a mixture E; Step 4.6, placing the mixture E into a vacuum extruder, and extruding it at an extrusion pressure of 3.6 to 5.0 MPa and an extrusion speed of 500 mm / min to 1000 mm / min to obtain a green body; Step 4.7, drying the green body at 50° C. to 80° C. for 2 to 5 hours until the moisture content of the green body is less than 2%, thereby obtaining a dried green body; Step 4.8, keeping the dried body at 500°C to 550°C for 8h to 12h to obtain a coal gangue matrix.

7. A high specific surface area denitration catalyst coal gangue matrix, characterized in that: The gangue matrix is ​​prepared by the preparation method described in any one of claims 1 to 6.